Penggunaan Model Pembelajaran Predict Observe Explain untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik - Ihsan Khoirul Anam; Epon Ningrum; Iwan Setiawan (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2024)
Learning models that can develop critical thinking skills include the Predict Observe Explain learning model. The aim of this research is to analyze the effect of using the Predict Observe Explain learning model on critical thinking skills at Senior High School 1 Bandung. This research uses an experimental research method with a quasi experimental design (none quivalent groups pretest-posttest design). Data collection was carried out using tests, giving assignments, and observation sheets. The research variable is the Predict Observe Explain learning model as the independent variable (X) while critical thinking ability is the dependent variable (Y). The subjects in this research were students in class XI IPS Senior High School 1 Bandung. Data analysis used Paired t-test and Simple Linear Regression. The research results show that: 1) there are differences in the critical thinking abilities of students in the experimental class before and after using the Predict Observe Explain learning model; and 2) there is an influence of using the Predict Observe Explain learning model on students critical thinking abilities in the experimental class.